Sculpture, sculpteurs et ateliers (?) à Chambéry et alentour (vers 1480-v. 1530) - Laurence Riviere Ciavaldini (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper is the critical account of some of the contributions of the thesis defended by Me S. Boisset-Boisset on medieval sculpture in Western Savoy, 1480-1530, at Grenoble Alpes University, in November 2015. It is supported by a rigorous investigation on a corpus of approximately 300 statues or groups of sculptures in which the author identified original series such as the Savoyard Virgin of Pity or quality works dedicated to local saints of international renown such as St. Anthony in Vienna (France). The meticulous formal analysis of the sculptures led her to isolate a group of forty-five witnesses from workshops or itinerant artists produced in the Chambéry region. The commissioners of these works could be the officers of the ducal administration, living in Chambéry and the surrounding area, the city still being the administrative and political capital of the duchy of Savoy.